REINTERPRETASI AYAT-AYAT EKOLOGI PERSPEKTIF MAQASID AL-QUR’AN FORMULASI ETIKA QUR’ANI UNTUK MERESPON KRISIS LINGKUNGAN - Pohan, Nanda; Erlangga saputra (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2025)
Cases of environmental pollution continue to rise resulting in an environmental crisis The impact not only destroys the beauty of nature and damages ecosystems but also threatens the lives of living creatures on earth From an Islamic perspective this crisis is not only a threat but also touches on eco theological aspects that should be considered by Muslims This study will examine ecological verses in the Quran and environmental ethics in order to prevent damage and bring benefits to fellow living creatures Through the maqasid al Quran approach to selected verses Al-Baqarah 30 Al Araf 56 Ar Rahman 7 9 his study will reveal the existence of these verses in an ecological context Data collection was carried out through library research which involved reviewing all literature related to the title and then drawing relevant conclusions This study concludes that the verses interpreted through the maqasid al Quran approach indicate the noble concepts and meanings behind the Quranic verses on ecology These include the concepts of khalifah fasad and mizan These three concepts are essentially interrelated and provide a moral framework for managing the environment Thus these concepts will give rise to environmental ethics that can be implemented through ecological responsibility protection and justice This verse provides concrete solutions for managing the environment It manifests itself in ecological education social movements and public policies that support nature conservation